2005
DOI: 10.7202/011308ar
|View full text |Cite
|
Sign up to set email alerts
|

Effet réservoir sur les âges 14C de la Mer de Champlain à la transition Pléistocène-Holocène : révision de la chronologie de la déglaciation au Québec méridional

Abstract: Résumé L’âge de macrorestes de plantes terricoles et une extrapolation fondée sur le pollen des sédiments sous-jacents à la date basale du lac postglaciaire de Hemlock Carr (243 m), au mont Saint-Hilaire, montrent que la déglaciation locale y est survenue vers 11 250 ans 14C BP (13,3-13,1 ka BP). La datation croisée entre de tels macrorestes (10 510 ± 60 ans 14C BP) et des coquilles de sédiments marins (~12 200 ans 14C BP) piégés au fond du lac Hertel (169 m), voisin, affiche un écart d’environ 1700 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 81 publications
0
28
0
1
Order By: Relevance
“…Mott and Farley-Gill (1981) calculated a 415 years hard water effect on gyttja from a lake south of the moraine, and Richard et al (1997) in the Gaspé Peninsula, Anderson et al (2001) in the Témiscamingue area and Occhietti and Richard (2003) at Mont Saint-Hilaire have confirmed that 14 C ages from basal gyttja can be up to 2000 years older than the enclosed terrestrial organic debris. With AMS dating on small samples, the ages of terrestrial plant debris are now the reference ages which reflect directly the past atmospheric 14 C content during the growth of the plants.…”
Section: Methodsmentioning
confidence: 74%
See 2 more Smart Citations
“…Mott and Farley-Gill (1981) calculated a 415 years hard water effect on gyttja from a lake south of the moraine, and Richard et al (1997) in the Gaspé Peninsula, Anderson et al (2001) in the Témiscamingue area and Occhietti and Richard (2003) at Mont Saint-Hilaire have confirmed that 14 C ages from basal gyttja can be up to 2000 years older than the enclosed terrestrial organic debris. With AMS dating on small samples, the ages of terrestrial plant debris are now the reference ages which reflect directly the past atmospheric 14 C content during the growth of the plants.…”
Section: Methodsmentioning
confidence: 74%
“…9500 BP) at the Saint-Nicolas site, 14 C ages from littoral shells are at least 350 years older than 14 C ages from wood (Occhietti et al, 2001a; Table II). This ᭝R does not apply necessarily to all the basin, as demonstrated by two other crossdatings from samples of Mont Saint-Hilaire and its vicinity (Table II) where the additional local reservoir effect reaches 700 and 1170 years Occhietti and Richard, 2003;Richard and Occhietti, 2005; Table III). During Younger Dryas, the oceanic reservoir effect was greater than at present, with apparent 14 C normalized ages older by 700-800 years rather than 400 years (Bard et al, 1994).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Géographie physique et Quaternaire, 60 (2), 2006 (Beta-27511) from a sandpit on the south side of Mont-SaintHilaire, Québec, seems unusually young and should be reassessed (Harington, 1988(Harington, , 2003a(Harington, , 2003b; and see dates on marine samples in Table III of Occhietti and Richard, 2003). (Watson, 1981;McAlpine et al, 2001;Kovacs, 2005).…”
Section: Radiocarbon Agementioning
confidence: 99%
“…At its best, EA can be a vital process in support of more sustainable forms of development, and that will happen only through the careful documentation and critical analysis of experience such as that offered in this timely text. (Laub et al, 1988 (Occhietti et Richard, 2003 ;Richard et Occhietti, 2004). Cette filiation paléogéographique et la pré-sence d'indices de la culture Clovis trouvés récemment dans la région du lac Mégantic (Chapdelaine, 2004) (Miller, 1988).…”
mentioning
confidence: 99%